2018
DOI: 10.1371/journal.pone.0202404
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-support ventilation or T-piece spontaneous breathing trials for patients with chronic obstructive pulmonary disease - A randomized controlled trial

Abstract: BackgroundLittle is known about the best strategy for weaning patients with chronic obstructive pulmonary disease (COPD) from mechanical ventilation. Spontaneous breathing trials (SBT) using a T-piece or pressure-support ventilation (PSV) have a central role in this process. Our aim was to compare T-piece and PSV SBTs according to the duration of mechanical ventilation (MV) in patients with COPD.MethodsPatients with COPD who had at least 48 hours of invasive MV support were randomized to 30 minutes of T-piece … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 32 publications
0
36
0
2
Order By: Relevance
“…Sklar et al [3] recently pointed out that PSV significantly reduces the work of breathing and pressure-time product compared to the T-piece, which could, in turn, more closely represent the post-extubation scenario. However, noninvasive mechanical ventilation (NIV) dissemination as an adjunctive for extubation makes clinical interpretation of these data difficult [24]. The major finding of our study suggests that both spontaneous breathing using T-piece and PSV are suitable methods for successful extubation of patients with critical illness from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Sklar et al [3] recently pointed out that PSV significantly reduces the work of breathing and pressure-time product compared to the T-piece, which could, in turn, more closely represent the post-extubation scenario. However, noninvasive mechanical ventilation (NIV) dissemination as an adjunctive for extubation makes clinical interpretation of these data difficult [24]. The major finding of our study suggests that both spontaneous breathing using T-piece and PSV are suitable methods for successful extubation of patients with critical illness from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 91%
“…The search strategy identified 2090 studies, and the data were from 10 RCTs comprising 3165 patients (Table 1) [10,[16][17][18][19][20][21][22][23][24]. The characteristics of the included studies are shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 99 patients met the inclusion criteria and all were recruited into the study (Figure 3). The eligible patients were male (50.51%) with the median age of 70 [23]…”
Section: Study Participantsmentioning
confidence: 99%
“…Practically, SBT is considered as a standard and effective weaning method 16,17 which consists of low-level pressure support ventilation (PSV) and T-piece. The majority of previous randomized controlled trials of different weaning methods demonstrated the similar extubation outcomes between the PSV and T-piece 18,19,[21][22][23][24][25] . In contrast, the recent multicenter study from Spain 27 showed a significantly higher rate of successful extubation in the PSV, compared with the T-piece (82.3% in the PSV group and 74% in the T-piece group, p=0.001) but showed the similar rates of reintubation (11.1% in the PSV group and 11.9% in the T-piece group, p=0.630).…”
Section: Introductionmentioning
confidence: 99%